The job security of employees of financially distressed companies - Loubser, Mieka E.; Garbers, Christoph (South African Mercantile Law Journal, 2021)
This contribution considers the legislative regulation of the job security (which boils down to preservation of employment) of employees in case of financial distress of a company. It juxtaposes the legislative regulation of four interrelated processes a company may engage in where it finds itself in financial distress, namely a voluntary internal restructuring (especially retrenchment), the transfer of the business or part of the business, business rescue and winding up. The legislative endeavour to preserve the job security of employees in all these processes is described and analysed. The discussion shows that room exists for companies to circumvent this protection and, to the extent that the protection does apply, that it remains difficult for employees to ultimately challenge the substance of decisions negatively affecting their job security. The main protection for employees in all these processes is procedural in nature and to be found in their rights to be informed of and consulted prior to decisions negatively affecting them. In this regard, business rescue is the most employee-friendly process. Participation in this process by employees, however, requires a fine balance as it may be self-defeating and lead to winding up and the permanent loss of jobs.
Keywords: Business rescue; Dismissal; Insolvency; Job security; Labor laws and legislation; Liquidation; Merger; Operational requirements; Retrenchments; Transfer of a business

Optimising the legal regulation of circular labour migration between South Africa, Lesotho and Zimbabwe - Matete, P. (North-West University, 2021)
Circular labour migration is steadily gaining prominence the world over, primarily due to the benefits it offers to the migrants, to the sending country, and to the receiving country – the so-called "triple-win" benefits. In order to enhance the benefits of circular labour migration, both the International Labour Organisation and the International Organisation for Migration recommend that adequate instruments of governance should be utilised. From the outset, this thesis recognises bilateral labour arrangements as the ideal instruments for enhancing the potential benefits that circular labour migration offers to the stakeholders involved in the process. As far as could be established, there has been no comprehensive research that seeks to provide insights on how the selected countries in the Southern Africa Development Community (South Africa, Lesotho and Zimbabwe) could optimise the benefits of circular labour migration for all stakeholders, primarily through the use of bilateral labour arrangements. The need for these insights in Southern Africa is pertinent due to the absence of a contemporary and clear framework regulating circular labour migration in the region. Based on the foregoing, this thesis advances the proposition that the guidelines provided by international law and standards of labour migration, and the best practices in Spain and New Zealand, can provide significant insights on how South Africa, Lesotho and Zimbabwe can enhance the regulation of circular labour migration to provide optimised benefits for all stakeholders. Proceeding from the above premise, this thesis makes a number of findings. These include the affirmation that bilateral labour arrangements are indeed the key regulatory instruments for promoting the triple-win benefits that circular labour migration offers; that circular labour migration, if managed well, plays an instrumental role in development in both the sending countries and the receiving countries; and that three key areas should be addressed in bilateral labour arrangements in order to effectively promote triple-win benefits. The three key areas that need to be addressed in bilateral labour arrangements in order to enhance the benefits for all stakeholders are linking migration with development, migration governance, and the protection of the rights of migrant workers. This thesis outlines the various principles that are necessary to give effect to these three key areas. This thesis finds that, based on the guidelines provided by international law and standards, it is essential that bilateral labour arrangements, at the minimum, incorporate provisions that facilitate skills training, the return and reintegration of migrants, the transfer of remittances, and the promotion of human resources development. In this regard, this study finds that the bilateral labour arrangements between South Africa and its neighbours, Lesotho and Zimbabwe, fall short of the guidelines provided by international law and standards on labour migration and by the best practices in New Zealand and Spain. The original contribution of this study lies in it being the first study to comprehensively explore the legal measures that South Africa, Lesotho and Zimbabwe could utilise to optimise the regulation of circular labour migration to South Africa as the main receiving country in SADC. This study makes recommendations on how the labour migration legal framework between the three countries can be improved, based on lessons learned from international law and standards on labour migration and best practices from selected countries.
Keywords: Bilateral arrangements; Circular labour migration; Droit du travail; Labour law; Migrant workers; Remittances; Travailleur migrant